2017
DOI: 10.1161/circoutcomes.117.004037
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic Heart Disease Treatment Cascade in Uganda

Abstract: Background Rheumatic heart disease (RHD) is a leading cause of premature death and disability in low-income countries; however, few receive optimal benzathine penicillin G (BPG) therapy to prevent disease progression. We aimed to comprehensively describe the treatment cascade for RHD in Uganda in order to identify appropriate targets for intervention. Methods and Results Using data from the Uganda RHD Registry (n=1,504), we identified the proportion of patients in the following care categories: (1) diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…One of the main barriers to expansion of cardiac surgery for RHD in low and lower-middle income countries (LLMICs) in sub-Saharan Africa is concern regarding the quality of follow-up. 11 12 After cardiac surgery, patients with RHD require penicillin prophylaxis for prevention of rheumatic fever recurrence, and most patients will also require anticoagulation to prevent thromboembolic events in the setting of a mechanical prosthesis and/or atrial fibrillation. 13 In the few LLMICs in the region that have established cardiac surgery programmes, follow-up has been done by cardiologists at major referral centres.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main barriers to expansion of cardiac surgery for RHD in low and lower-middle income countries (LLMICs) in sub-Saharan Africa is concern regarding the quality of follow-up. 11 12 After cardiac surgery, patients with RHD require penicillin prophylaxis for prevention of rheumatic fever recurrence, and most patients will also require anticoagulation to prevent thromboembolic events in the setting of a mechanical prosthesis and/or atrial fibrillation. 13 In the few LLMICs in the region that have established cardiac surgery programmes, follow-up has been done by cardiologists at major referral centres.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, providers felt that it was important to develop metrics around how the system was functioning and whether specific interventions might work. Here again, we borrowed from HIV/AIDS models to create the RHD Treatment Cascade ( Figure 3 ) [ 27 ]. We found that retention in care was the most significant barrier along the cascade, while rates of optimal adherence to benzathine penicillin G were high among those patients who were retained in care [ 27 ].…”
Section: Delivering Valuementioning
confidence: 99%
“…Here again, we borrowed from HIV/AIDS models to create the RHD Treatment Cascade ( Figure 3 ) [ 27 ]. We found that retention in care was the most significant barrier along the cascade, while rates of optimal adherence to benzathine penicillin G were high among those patients who were retained in care [ 27 ]. Our analysis also showed that distance to a local health center and access to a regional RHD center of excellence were associated with improved retention and adherence, suggesting that our efforts to decentralize care had significant impact on these care quality metrics [ 27 ].…”
Section: Delivering Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Successful prevention of ARF and control of RHD involve treatment of streptococcal infection (primary prevention), regular administration of penicillin to prevent recurrences of ARF (secondary prevention), and medical and surgical treatment of patients with complications of RHD (tertiary prevention) [5]. A variety of different types of data, including human resources for health publications, primary care studies (focused primarily on infectious diseases), the REMEDY (Global Rheumatic Heart Disease Registry) study [8,9], and qualitative research on RHD barriers in Uganda, all point to human resources as a likely key bottleneck for ARF/RHD care [10]. Specific data on ARF/RHD care are not widely available, but severe human resource shortages have been documented in LMIC for a wide range of health conditions [11] and, because RHD is especially neglected and nonprioritized in most countries, it is likely that bottlenecks are even more pronounced for this particular condition [12].…”
mentioning
confidence: 99%